Health promotion and quality of life for adolescents pregnant women in riverine communities: The intervention of nursing in prenatal care (Research, Society and Development, 2026)
Introduction: Adolescent pregnancy in riverside communities constitutes a significant public health challenge, aggravated by social vulnerabilities, difficulties in accessing health services, and geographical limitations. Objective: To analyze the contribution of nursing interventions in prenatal care to the promotion of health and quality of life of pregnant adolescents in riverside communities. Methodology: This is a qualitative, descriptive, and exploratory study, conducted through a narrative literature review, consulting scientific publications and official documents published between 2015 and 2025. Results: It was evidenced that the nurse's role in prenatal care, through educational actions, qualified listening, home visits, and continuous monitoring, favors adherence to consultations, early identification of gestational risks, and improvement in the physical and emotional well-being of adolescents. Conclusion: It is concluded that nursing plays a fundamental role in promoting maternal and child health in riverside communities, and it is necessary to expand public policies that strengthen prenatal care for this population.